M14 A multi-site online cross-sectional survey assessing influenza vaccination uptake among london medical students and modifiable factors influencing this. (15th November 2016) - Pankin, GA; Jackson, NE; Patel, IS; Patel, AS
Abstract : Introduction and objectives: Around 1 in 5 healthcare workers (HCWs) may become infected during the influenza (flu) season and between 28–59% will have subclinical illness which they could pass on to those more vulnerable. As a result, annual vaccination against flu is recommended for all UK National Health Service staff. However, during the 2015/16 season only 55% of HCWs with direct clinical roles were vaccinated, with lower than average rates seen in London. Like any HCW, medical students should be actively encouraged to get vaccinated. Our aim was to assess levels of flu vaccine uptake among London medical students and investigate the negative influences affecting uptake that could be addressed at an institutional level. Methods: A cross-sectional online survey, developed by a focus group of respiratory consultants and medical students, was disseminated to London medical students at King's College Hospital, Guy's and St Thomas' Hospitals and University Hospital Lewisham. Data was collected and analysed using SurveyMonkey Inc. Results: 302 medical students completed the survey (Table 1 ). There was a good representation of students across different sites and clinical years. Overall, 44% students reported receiving the flu vaccine. Uptake varied between teaching sites and clinical years. 82% of students felt they should get vaccinated with 51% of those doing so. 64% of those who were not vaccinated said they were not offered it, of whom 73% felt vaccination was appropriate. 50% of all students said they were not provided with any information about the vaccine. 68% of those who were provided with information were vaccinated whereas 20% of those who were not provided with information were vaccinated. Conclusions: Vaccination rates among London medical students are lower than for most HCWs. There appears to be a discrepancy between willingess to get vaccinated and actual uptake rates. This may be due to a lack of information and encouragement rather than a lack of access, as 72% of all students were aware of how to access the vaccine. Teaching hospitals and the University should address this by introducing flu vaccination awareness into the curriculum and consider adding it to mandated occupation health assessments.